Pengaruh Likuiditas, Profitabilitas, dan Free Cash Flow Pada Kebijakan Dividen (Studi Pada BUMN Tahun 2015-2019) - Fatchur Rochman; Rizky Agustin (JAMER : Jurnal Akuntansi Merdeka, 2021)
This reserch intend to decide the influence of liquidity, profitability and free cash flow (FCF) at dividend policy. The sampling technique untized was purposive sampling method. The secondary data were obtained from from the yearly report of 11 stateowned enterprises that were registered on the Indonesia Stock Exchange for 2015 - 2019. The multiple regression by the SPSS V-16.00 program was performed using for data analysis. The yield indicated that partly the liquidity and free cash flow variables did not had significant effect on dividend policy, the profitability variable had a significant effect on dividend policy. Simultaneously the variable ol liquidity, profitability and FCF indicated a significant effect on dividend policy at stateowned enterprises that are registered on the Indonesian Stock Exchange in 2015 - 2019.